Effect of rapid high-intensity light curing on micro-leakage in conventional and bulk-fill resin composites - Lu, Yaojia; Cai, Qi; Zhou, Dongyan (Frontiers in Materials, 2025)
PurposeThis study compared the effect of high-intensity (3,200 mW/cm2) and conventional-intensity (1,000 mW/cm2) light curing on the micro-leakage properties of conventional and bulk-fill resin composites.MethodsCavities were respectively prepared on the mesial and distal surfaces of 60 molars. 3M™ Filtek™ One Bulk Fill Restorative (BF), 3M™ Filtek™ Z350 XT Universal Restorative (Z350), and 3M™ Single bond universal adhesive were used to fill the molars with different light-curing modes. After temperature cycling, staining, and sectioning, the micro-leakage of these teeth was observed with a microscope.ResultsIn the condition of adhesive at standard power, the micro-leakage of BF in both light-curing irradiation modes showed no significant differences (P > 0.05), and that of Z350 was significantly increased following high-intensity irradiation (P < 0.05). Compared with the standard mode, the micro-leakage was significantly higher (P < 0.05) for both BF and Z350 under the condition of high-intensity irradiation for adhesive.ConclusionA high-power and short-duration light mode is not suitable for all materials. The selection of the light-curing mode should be based on the material composition and physicochemical properties, determining the appropriate irradiation time and intensity to minimize micro-leakage in resin-based restorative materials and thereby ensure a favorable restoration prognosis.